Development of a healthy cookie to promote toddlers' brain development: Brainy Bites / Airin Fatehah, Naleena Devi - Airin Fatehah, Aziz; Naleena Devi, Muniandy (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
This study aims to develop a healthy cookie designed for toddlers. "Brainy Bites" was developed by incorporating ingredients that are linked with healthy brain development and improved cognitive function in early childhood. Proximate analysis revealed that Brainy Bites contain 67.71 ± 0.23 carbohydrate, 3.87± 0.07 crude protein, 18.51 ± 0.24 fat, 1.80 ± 0.01crude fiber, 1.63 ± 0.01 ash and 8.29 ± 0.10 moisture. Physical analysis done on Brainy Bites indicated that the developed cookie had 0.5 cm thickness, 3.7 cm width, 7.4 spread ratio, 18.18% bake loss and 1392.4 g hardness, respectively. There were significant difference (p < 0.05) in the nutrients content of Brainy Bites and the two cookies that were compared in which Brainy Bites contains significantly higher amount of crude protein, crude fiber and ash content . Brainy Bites will serve as a great snack for toddlers at home, nurseries or for travelling. The cookie will be accepted in the market and would be a better choice of snack for toddlers as it contains no added sugar and salt, and contains ingredients such as raisins, almonds and chia seeds that may help in the brain development among toddlers.